2010
DOI: 10.3816/cbc.2010.n.062
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Adjuvant Zoledronic Acid in Postmenopausal Women With High-Risk Breast Cancer

Abstract: Purpose We present the results of a randomized, multicenter clinical trial of adjuvant ZA in postmenopausal women with high-risk breast cancer. The primary objective was change in bone mineral density (BMD) at the lumbar spine and femoral neck at 1 year. Secondary objectives included change in calcaneal BMD, disease-free survival (DFS), overall survival (OS), and toxicity. Patients and Methods Postmenopausal women with stage II/III breast cancer diagnosed up to five years prior were eligible and randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…In eight trials (10,927 patients) an N-BP was tested (zoledronic acid, pamidronate, ibandronate or risedronate) [12][13][14][15][16][17][18][19]. In the clodronate trial subset, patients treated with antiresorptive therapy had a nonsignificant reduction in the risk of death compared with those in the control arms (HR of death: 0.86; 95% CI: 0.67-1.11), with a strong heterogeneity (I 2 = 61%) driven by a single trial [8].…”
Section: An Explorative Meta-analysis To Assess the Efficacy Of Diffementioning
confidence: 99%
See 1 more Smart Citation
“…In eight trials (10,927 patients) an N-BP was tested (zoledronic acid, pamidronate, ibandronate or risedronate) [12][13][14][15][16][17][18][19]. In the clodronate trial subset, patients treated with antiresorptive therapy had a nonsignificant reduction in the risk of death compared with those in the control arms (HR of death: 0.86; 95% CI: 0.67-1.11), with a strong heterogeneity (I 2 = 61%) driven by a single trial [8].…”
Section: An Explorative Meta-analysis To Assess the Efficacy Of Diffementioning
confidence: 99%
“…To provide information on the effect of adjuvant N-BPs compared with clodronate on survival in early breast cancer, we performed a literaturebased meta-analysis of 12 randomized prospective trials comparing different BPs with either placebo or no antiresorptive therapy [8][9][10][11][12][13][14][15][16][17][18][19]. For all of these studies, data on OS were reported in the most updated publication.…”
Section: An Explorative Meta-analysis To Assess the Efficacy Of Diffementioning
confidence: 99%
“…We appraised the rate of patients lost to follow up and in the majority of the studies the rate was <10%. In three trials the rate was higher (Range – 17–42%; [19][20], [28]). …”
Section: Resultsmentioning
confidence: 87%
“…Ten trials (13,571 patients) were eligible for the meta-analysis of overall survival [13][17], [19], [22], [24], [28]–[29]. The numbers of randomly assigned and analyzed patients in each included trial are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the completed trials investigated adjuvant bisphosphonate therapy for its effect on bone health [7][8][9][10][11][12] . Those trials often compared early with delayed bisphosphonate therapy rather than adjuvant za with no bisphosphonate, or considered primary endpoints that were unrelated to breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%